Pendampingan Al-Qur’an dengan Metode Tilawati sebagai Upaya Meningkatkan Kemampuan Baca Tulis Al-Qur’an - Alek Sander; Martin Kustati; Gusmirawati Gusmirawati (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2025)
The ability to read and write the Qur’an is a fundamental skill that every Muslim should possess. However, in reality, many children and adolescents still cannot read the Qur’an properly and accurately according to tajwid rules. This mentoring program aims to enhance students' ability to read the Qur’an in a tartil manner (slowly, clearly, and correctly) following tajwid rules, train and develop their skills in writing Hijaiyah letters and Qur’anic verses accurately, foster motivation, interest, and love for the Qur’an from an early age, and evaluate the effectiveness of implementing the Tilawati Method in Qur’anic literacy mentoring. The program employs a Participatory Action Research (PAR) approach, actively involving teachers, students (santri), and mentors in every stage: problem identification, planning, implementation, evaluation, and reflection. Results show that the Tilawati Method is effective evidenced by significant improvement: 18 out of 20 students could read the Qur’an fluently, 17 could write Hijaiyah letters correctly, and 16 could memorize five short surahs with tartil. The method was applied through talaqqi and musyafahah approaches, where students read directly in front of mentors, allowing immediate correction of reading errors. Mentoring was conducted progressively from introducing Hijaiyah letters, practicing tartil reading, to improving fluency in reciting Qur’anic verses. In conclusion, Tilawati-based mentoring is effective in enhancing basic Qur’anic reading skills and can serve as a strategic approach for Qur’anic education in TPQs (Qur’anic Learning Centers) and other Islamic educational institutions.